Legalizing software for measuring instruments : a proposed plan for Malaysian case study - Muhammad Azwan Ibrahim,; Nazri Marzuki,; Osman Zakaria,; Zarina Shukur,; Nasharuddin Zainal,; Maryati Mohd. Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Software has become one of the most critical parts of a measuring instrument. Despite the sophistication and complexity of measuring instruments, legal metrology framework on software remains poor. Several legal cases related to the manipulation and modification of software used in measuring instruments have been discovered in ASEAN countries, particularly in Malaysia. A survey has been conducted and findings show that most ASEAN countries have yet to implement and enforce legal metrology control on the software in their metrological system. This paper discusses an approach to legalizing software for measuring instruments in the Malaysian context.